In Vitro Evaluation of the Antifungal Effect of AgNPs on Fusarium oxysporum f. sp. lycopersici - Karla Lizbeth Macías Sánchez; Hiram Deusdedut Rashid González Martínez; Raúl Carrera Cerritos; Juan Carlos Martínez Espinosa (Nanomaterials, 2023)
The application of nanomaterials in the agri-food industry can lead us to the formulation of new sustainable and effective pesticides for the control of fungi such as Fusarium oxysporum f. sp. lycopersici (Fol). This is a fungal plant pathogen for the tomato plant. In this work, silver nanoparticles (AgNPs) were synthesized by a green methodology from Geranium leaf extract as a reducing agent. The poisoned food technique was used to determine the percentage of inhibition of Fol mycelial growth by the action of AgNPs. They were characterized by transmission electron microscopy (TEM, JEOL JEM-2100, Tokyo, Japan) and ultraviolet-visible spectroscopy (UV-VIS, DU 730 Beckman Coulter, Brea, CA, USA). Five different concentrations of AgNPs (10, 20, 40, 75, and 150 mg/L) were evaluated in vitro in order to determine the minimum inhibitory concentration (MIC) as well as the behavior of their antifungal activity in tomato fruit. Nanoparticles with spherical morphology and average diameters of 38.5 ± 18.5 nm were obtained. The maximum percentage of inhibition on the mycelial growth of Fol was 94.6 ± 0.1%, which was obtained using the AgNPs concentration of 150 mg/L and it was determined that the MIC corresponds to 75 mg/L. On the other hand, in a qualitative way, it was possible to observe an external inhibitory effect in the tomato fruit from the concentration of 10 mg/L. Finally, we can conclude that AgNPs are a viable alternative for alternative formulations applied in the agri-food industry as pesticide solutions.